Epibrassinolide Triggers Apoptotic Cell Death in SK-N-AS Neuroblastoma Cells by Targeting GSK3β in a ROS Generation-Dependent Way - Pınar Obakan Yerlikaya; Shafaq Naxmedova (European Journal of Biology)
Objective: Epibrassinolide (EBR), a biologically active member of the brassinosteroids plant hormone family, has been recently indicated as an apoptotic inducer in various cancer cells without affecting non-tumor cell proliferation. Glycogen synthase kinase 3β (GSK3β) was the first identified molecule that acts as a critical mediator of glycogen metabolism and insulin signaling mechanism. GSK3β has been described as an essential factor for tumor progression by phosphorylating and inactivating the pro-apoptotic family member of the Bcl-2 family, Bax. It was recently shown to regulate cell division, differentiation, and adhesion. Materials and Methods: To investigate the relative cell viability affected by EBR treatment and the preventive effect of N-acetyl cysteine (NAC) we performed MTT assay and FACS analysis, respectively. Colony formation and soft agar techniques were used to understand the inhibitory effect of EBR on colony formation and diameters. Annexin V-PI analysis by flow cytometry was performed for the measurement of the apoptotic cell percentages. Fluorescence microscopy was performed for the determination of mitochondria membrane potential following DiOC6 staining. The expression profiles of apoptotic proteins, as well as GSK3β and β-catenin were investigated by immunoblotting. Results: Our results indicated that EBR induced mitochodria-mediated apoptosis by inducing ROS generation which can be prevented by NAC, a reactive oxgen species scavenger. EBR-induced apoptosis can influence the inhibitory phosphorylation of GSK3β by Ser9 and prevents the translocation of the down-stream target, β-catenin. Conclusion: This study evaluated EBR as a potential apoptotic inducer in neuroblastoma cell line SK-N-AS and investigated the GSK3β involvement.